Harnessing the maximum reinforcement of graphene oxide for poly(vinylidene fluoride) nanocomposites via polydopamine assisted novel surface modification. Issue 74 (22nd July 2016) - Roy, Sunanda; Das, Tanya; Zhang, Liying; Hu, Xiao Matthew
Abstract : Sequential modification of graphene oxide through mussel-inspired chemistry, thiol-ene chemistry and Michael addition reaction. Abstract : Surface modification of graphene oxide (GO) is imperative in modern composite research progress due to its poor surface chemistry. However, a facile, scalable and appropriate functionalization process which empowers molecule-level dispersion and maximum interfacial interaction between matrix and nanofiller at lowest loading is a major challenge up to now. This paper presents a novel functionalized GO through a combination of mussel-inspired chemistry, thiol-ene chemistry and Michael addition reaction with the aim to overcome the aforementioned problems and harness the maximum capability of GO to fabricate advanced nanocomposites. The functionalization process is carried out through a simple, fast and environmental-friendly way and is capable of producing a large quantity of highly exfoliated reactive GO. The modified GO displayed substantial interactions and excellent dispersion when incorporated into poly(vinylidene fluoride) (PVDF) matrix, leading to attain super strong, tough and thermally stable PVDF nanocomposites even at only 0.4 wt% filler loading. Furthermore, the functionalized GO renders outstanding barrier performance and durability to the composite coatings while being tested under various harsh conditions. The nanocomposites are noted to retain their original strength even when subjected to hot seawater for 60 days. Hence, we believe that this approach could open a new avenue to explore GO for other new age polymer nanocomposites with multifunctional capability.